PERANCANGAN SISTEM KERJA PENERANGAN JALAN UMUM MENGGUNAKAN TENAGA SOLAR CELL BERBASIS INTERNET OF THINGS - Oktavia, Bela; Amperawan (Teknik Elektro Polsri, 2024)
This research discusses the design of a public street lighting system utilizing a 50 Wp solar cell, an 18 Ah battery at 12V, an ESP32 microcontroller, an LDR sensor, an INA219 sensor, and the Blynk platform for monitoring. The system is designed to provide an efficient and eco-friendly lighting solution by harnessing renewable energy from solar panels. The main components of the system include a solar panel that converts solar energy into electricity and stores it in the battery for nighttime use. An LDR (Light Dependent Resistor) sensor is used to detect ambient light intensity, allowing the system to automatically turn on the lights at night and turn them off during the day. The INA219 sensor functions to measure the voltage and current flowing from the solar panel to the battery and from the battery to the light, ensuring efficient energy management. The ESP32 microcontroller serves as the brain of the system, integrating data from the LDR and INA219 sensors to control light operations and send data to the Blynk platform. Blynk is used as a remote monitoring system.